Analysis of soil fertility status on rice (Oryza sativa L.) planted land in Polewali District, Polewali Mandar Regency - Numba, Sudirman; Haris , Abdul; Saidah; Haris, B. Ibrahim; Ashar , Jabal Rahmat; Hari Sucipto , Muh. Ibnu (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Rice is the main food commodity in Indonesia. The main abiotic factor affecting rice productivity is soil fertility. This study aimed to determine the soil fertility status (SFS) of paddy fields in Polewali District, Polewali Mandar Regency, West Sulawesi. The research was conducted by surveying soil characteristics supported by soil chemical analysis at the Laboratory of Soil Science and Environmental Conservation, Faculty of Agriculture, Universitas Muslim Indonesia. The research was conducted in Polewali District, with the survey area consisting of 4 land map units (LMU). Soil fertility status was determined based on the criteria of each soil fertility parameter, namely: soil pH, organic C-content, cation exchange capacity, available P, Potassium content, and base saturation. The results showed that the SFS in Polewali District was classified as low. Only the base saturation parameters in LMU-2 and LMU-3 were classified as high. In addition, all parameters were only classified as very low to medium at all LMUs. Low C-organic content and very low P and K content are the main limiting factors for SFS. Recommended land management to improve soil fertility is the addition of organic matter that can increase total nitrogen and C-organic in the soil and the application of manure. Keywords: Soil fertility status, paddy fields, rice plants